2014
DOI: 10.1080/09205063.2014.884427
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-hydroxybutyrate-co-3-hydroxyvalerate)-based nanofibrous scaffolds to support functional esophageal epithelial cells towards engineering the esophagus

Abstract: Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and PHBV-gelatin were electrospun to obtain defect-free nanofibers by optimizing various process and solution parameters. Tensile strength, Young's modulus, and wettability of PHBV-gelatin nanofibrous scaffold were determined and compared with PHBV nanofibrous scaffold. Our results demonstrate that PHBV-gelatin nanofibers exhibited higher tensile strength and Young's modulus than the PHBV nanofibers. Human esophageal epithelial cells (HEEpiC) were cultured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The proliferation of cells was determined aer 1, 3 & 10 days using MTS assay (CellTiter 96 AQueous one solution, Promega, USA). 25 At the end of each time point, the samples were washed with D-PBS solution to remove the non-adherent cells. Serumfree media (1 mL) and 200 mL of MTS reagent were added to each well and incubated at 37 C for 2 hours.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
“…The proliferation of cells was determined aer 1, 3 & 10 days using MTS assay (CellTiter 96 AQueous one solution, Promega, USA). 25 At the end of each time point, the samples were washed with D-PBS solution to remove the non-adherent cells. Serumfree media (1 mL) and 200 mL of MTS reagent were added to each well and incubated at 37 C for 2 hours.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
“…32 Therefore, PHBV can be used in combination with other polymers such as PLLA, gelatin, collagen, chitosan, and silk to enhance degradability, 26,30 hydrophilicity, and biocompatibility. 26,30,3336…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al 16 dissolved PHBV in hexauoroisopropanol (HFIP), the ber diameter were 600 nm, and the cell culture experiments indicated that the PHBV nanobrous scaffold accelerated the adhesion and growth of NIH3T3 cells, thus making the former a good scaffold for tissue engineering. Kuppan et al 11,14 dissolved PHBV in a mixture of DCM and DMF (9 : 1) to form a 15% (w/v) solution. The average diameter of the PHBV bers was 724 nm.…”
Section: Introductionmentioning
confidence: 99%